Agreeing to Disagree: The Problems of the Traditional Approaches to the Interpretation of International Law - Maisley, Nahuel (2024)
People disagree about international law. To help them work through these disagreements, the discipline has developed a series of rules on the interpretation of its various sources—most notably, Articles 31 and 32 of the Vienna Convention on the Law of Treaties and the standards developed by the International Court of Justice and the International Law Commission for the identification of custom. The problem, however, is that these norms are themselves subject to disagreement, thereby creating a meta-debate about how to interpret the rules on interpretation. This Article delves into this meta-debate, focusing specifically on the views adopted by the “traditional approaches to international law”—that is, the mainstream, the default paradigm in the minds of most international lawyers. The Article makes two claims, one descriptive and one evaluative. Descriptively, it argues that the common trait among these seemingly uncoordinated views is that they see every discrepancy regarding the interpretation of international law ultimately as a purely empirical disagreement, meaning that it can be fully resolved through the verification of the existence or inexistence of certain social facts. Evaluatively, the Article argues that this empirical approach causes theoretical shortcomings, as it struggles to explain typical interpretive disputes in international law. This, in turn, leads to practical challenges in identifying genuine points of contention and facilitating resolution. These limitations, the Article concludes, diminish the interpretive usefulness of the traditional approaches and call for an alternative account. To process their disagreements, people typically need more than just facts: they need, instead, to exchange arguments about international law. Then, they may convince each other, and build agreements. Or, at least, quite importantly, they may agree to disagree.